Efektivitas Teknik Air Abrasion dan Teknik Poles Konvensional Terhadap Perubahan Warna Pada Resin Komposit Nanofiller : kajian setelah proses perendaman kopi robusta (Laporan Penelitian) - Dinda Lulu Afifah Himawan; Ade Prijanti Dwisaptarini (Jurnal Kedokteran Gigi Terpadu, 2021)
Background: Nanofiller composite resins are commonly used as a restorative materials but nanofiller composite resins has high susceptibility to stain. Coffee has a huge impact on color changes. Besides of being able to give a smooth surface of a composite resins, polishing techniques were able to remove superficial stain on composite resins. Air abrasion technique has been introduced since 1945 and is still being used not because its only ability to remove caries, but also its ability to remove superficial stain on the teeth. Aim: to discover the effectiveness of air abrasion technique and conventional polishing technique towards color changes in nanofiller composite resins that were immersed in robusta coffee. Materials and Method: Twenty samples were immersed in robusta coffee for 7 days. Samples that have been stained were devided into two groups, group one were polished with air abrasion technique and group two were polished with conventional technique using abrasive discs.The color changes measurement were taken using spectrophotometer VITA Easyshade V prior to and after staining, and then repeated after polishing treatment. Result: There were significant differences in L, C and E between before the samples were immersed in robusta coffee and after they were polished with air abrasion technique. But there were no significant differences between before the samples were immersed in robusta coffee and after they were polished with conventional technique. Conclusion: There were differences in the effectiveness of air abrasion technique and conventional polishing technique towards color changes in nanofiller composite resins that were immersed in robusta coffee.